The Medical Residency in Perú - Pamo-Reyna, Oscar G. (2019)
Since the start of medical residency in Peru, in 1952, there have been a number of changes that have become an increasingly integrated system. Currently, the Ministry of Health, which is the main support of medical residency, tries to meet the needs of medical specialists with a single annual competition through CONAREME, which is the management board of the National Medical Residency System. The strengths, opportunities, threats and weaknesses of the medical residency in our country are presented.